The Connection between the Madden-Julian Oscillation and European Weather Regimes and its Modulation by low frequency Forcings - Klaus, Seraina Tamara (ETH Zurich, 2017)
Progress in extended range numerical weather prediction for Europe relies on a correct representation of the large-scale midlatitude circulation which can be described by specific weather regimes for the Atlantic-European region. Therefore, it is important to understand their life cycles and identify processes that are responsible for their favoured occurrence, persistence or transition. Recent studies have shown that convectively active phases of the Madden-Julian Oscillation (MJO) in the tropics impact and control part of the distribution and sequences of the daily weather regimes defined over the North Atlantic-European region. Thereby, El Niño-Southern Oscillation (ENSO), the Pacific-North American teleconnection pattern (PNA), and the strength of the stratospheric polar vortex modulate the background states through which the MJO and its global response patterns propagate during Northern Hemisphere winter. Within this thesis, we here present how the frequency of defined Atlantic-European weather regime occurrences is modulated following an MJO activity. The lagged relationship between active MJO episodes and weather regime occurrences is explored for 37 extended winters from 1979 to present. We examined for unmodulated and modulated background states the potential predictability, focusing separately on the influence of ENSO, PNA and the strength of the stratospheric polar vortex. The results indicate that the lagged relationship between the MJO phases and the weather regimes strongly differs during different states of ENSO, PNA and the stratospheric circulation. Hence, the European response to MJO activity substantially changes with a varying background state. Our findings demonstrate the importance of considering both the MJO activity in its phase and the concurrent low frequency forcings to determine the statistically expected regime frequency due to a MJO event.